Comparative study of Mycobacterium tuberculosis and Mycobacterium bovis protein profiles - Sharifi Yazdi, Mohammad Kazem; Beheshtnejad, Amir Houshang; Hedayatpour, Azim; Sharifi-Yazdi, Sara; Mehrani, Fariborz (Journal of Surgery and Medicine, 2018)
Aim: Despite the drug resistance Mycobacterium bovis and Mycobacterium tuberculosis (MTB) are still regarded as two of the global health problems in the world. In the present study, a comparison was made between protein profiles of Mycobacterium bovis and MTB in order to achieve effective biomarkers for diagnosis of tuberculosis. Methods: The clinical samples, sputum and gastric lavage (and the other samples) were processed by N-acetyl-L-cysteine-sodium hydroxide methods and consequently were cultured on Lowenstein–Jensen medium. Mycobacterium tuberculosis and bovis strains were distinguished according to the biochemical tests and susceptibility testing system. Colonies were grown in 7H9 medium and membrane and secretory proteins were extracted, purified by ammonium sulfate and refrigerated alcohol methods. Results: The protein contents were measured by Bradford method. Comparison of protein bands in each strain were performed by one dimensional electrophoresis. The major discrepancy between the two strains in the banding separation membrane proteins could be observed in 45 and 60 KDa and also less than 45 and 14 KDa. Conclusion: The results showed that discrepancy in the proteins bands could be used as protein effective biomarker for tuberculosis diagnosis. We should use antibody against tuberculosis for further investigation for rapid tuberculosis diagnosis.